Effects of Heat Processing Techniques on Nutritional Value and in vitro Rumen Fermentation Characteristics of Jack bean (Canavalia ensiformis L.) - Prasetiyono, B.W.H.E.; Tampoebolon, B.I.M.; Subrata, A.; Widiyanto (Pakistan Journal of Nutrition, 2018)
Background and Objective: Feedstuffs that serve as protein sources for ruminants are expensive. Jack bean (Canavalia ensiformis L.) is an indigenous legume grown in Indonesia, which is rich in protein (23.95%), but is not used for protein supplementation in ruminants. This study on jack bean was conducted to improve its potential as a protein supplement for ruminants, jack beans were processed and evaluated for nutritional value and rumen fermentation characteristics. Methodology: Effects of no treatment (H0), compared to a roasting treatment (H1), an oven treatment (H2) and an extrusion treatment (H3) were investigated. Results: Heat processing techniques (H1, H2, H3) significantly (p